Analisis Pengaruh Warna Reflektor Antena Parabola Jenis Solid dan Mesh TerhadapKualitas Sinyal pada Aplikasi DVB-S - Hendri Lesmono; Khairi Budayawan; Yasdinul Huda (Universitas Negeri Padang, 2014)
Digital Video Broadcasting via Satellite (DVB-S) is a communications that use a satellites as a repeater signal from the sender to the receiver. Because it uses the satellite as a repeater signal , then in the sender and receiver use a parabolic antenna type. The majority of the current parabolic antenna reflector color comes from the color of the material used reflector itself is gray, while the use of other types of color are rarely used be it a lighten color or darken color, in addition to use of the parabolic reflector antenna at this point, especially for the type of solid is very susceptible to corrosion or rust. So it is necessary to research on the influence of color on quality parabolic reflector antenna signal that produce either from a parabolic type of solid or mesh type.This type of experimental research, in this researchers informant trying to observe and manipulated object under control. Informant painting on the parabolic reflector antenna, measuring signal quality, signal strength and the value of C/N and then compare the results of measurements on each color parabolic reflector antenna. Instruments used by informant is a parabolic antenna, Low Noise Block (LNB)and satellite meter.The results showed that the color of a parabolic reflector antenna isinfluence on signal quality and strength of the signal that received by the receiver. The more bright colors that used in parabolic reflector antenna, more electromagnetic waves are reflected toward the LNB satellite dish antenna and vice versa which have an impact on increasing the quality of the received signal at the receiver. Painting parabolic reflector antenna other than as an attempt to prevent corrosion are also could to improve the quality of the signal, with a record of using colors that have been suggested. Color parabolic reflector antennas are recommended for applications DVB - S is a white and light blue